1997
DOI: 10.1029/96jd02750
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Asian emissions on the remote North Pacific atmosphere: Interpretation of CO data from Shemya, Guam, Midway and Mauna Loa

Abstract: Abstract. In this study we look at the concentration of CO at four remote stations in the North Pacific to evaluate the impact of Asian industrial emissions on the remote atmosphere. Using a locally weighted smoothing technique to identify individual data outliers from the seasonal cycle, we have identified 22-92 outliers or "events" (greater than 5 ppbv above the seasonal cycle) at each site for the 3-6 year data records. Using isentropic back trajectories, we identify a possible source region for each event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 31 publications
4
60
0
Order By: Relevance
“…Again, this shows the sensitivity of the simulations to the prescribed deposition fluxes. Mauna Loa is also affected by the long-range transport of CH 3 ONO 2 from Asia, especially during spring (Jaffe et al, 1997). Such an increase can be seen around day 180 in both HIGHBR and FULL, but not for DEMISS, which is representative of northerly transport from pristine regions.…”
Section: Comparisons Against Surface and Aircraft Measurementsmentioning
confidence: 93%
“…Again, this shows the sensitivity of the simulations to the prescribed deposition fluxes. Mauna Loa is also affected by the long-range transport of CH 3 ONO 2 from Asia, especially during spring (Jaffe et al, 1997). Such an increase can be seen around day 180 in both HIGHBR and FULL, but not for DEMISS, which is representative of northerly transport from pristine regions.…”
Section: Comparisons Against Surface and Aircraft Measurementsmentioning
confidence: 93%
“…However, the back trajectories (during both events) indicated that the air mass passed over the fire events in the northwestern IGP. We note that using back trajectories to identify source regions is also uncertain, as noted by Jaffe et al (1997). Figure 8k shows model biomass CO peak coincident with observed CO.…”
Section: Diurnal Variations Of Air Pollutants and Boundary Layer Heightmentioning
confidence: 99%
“…Both periods show high CO, SO 2 , BC and PAN levels. The high levels of CO (Roths and Harris, 1996;Jaffe et al, 1997, Yurganov et al, 1998Ponchanart et al, 2003;Fisher et al, 2010) and aerosols (Haywood and Boucher, 2000;Zhao et al, 2002;Eck et al, 2003;Myhre et al, 2003;Massie e al., 2004, Abel et al, 2005Reid et al, 2005a, b;Forster et al, 2007) along with high levels of HCN observed by in situ data validate the biomass burning origin of the plumes. Moreover, SO 2 measurements are significantly above background levels in both part of the lower/middle tropospheric plume; these enhanced amounts suggest mixing of the biomass burning plume with anthropogenic pollution.…”
Section: In Situ Measurements Of Plume Chemical Compositionmentioning
confidence: 99%